Perjalanan Wisata Minat Khusus Geowisata Gunung Merapi ( studi di Lereng Merapi Bagian Selatan, Yogyakarta) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT: The characteristic of Merapi volcano as the most active volcano in the world will be an interesting special interest tourism. It's characateristic has been made volcanology phenomenon